Empirical Analysis of Starting Salaries of College Graduates based on Their University-Industry Cooperation Activities - Park, Mun Su (International Journal of Knowledge Content Development & Technology, 2023)
Fifteen years have passed since the enactment of the Industrial Technology Innovation Promotion Act, which promoted industry cooperation activities for universities. Therefore, the study analyzes the relationship between the university’s industrial cooperation activities and the college graduates’ starting salaries and provides policy suggestions on improving the direction of university-industry cooperation. The study used nine-year panel data from Graduates Occupational Mobility Survey (GOMS) to conduct an empirical analysis and found that starting salaries of college graduates were not significantly higher if the university only participated in basic industry cooperation activities. On the other hand, when the quality of university-industry cooperation activities was higher, such as job search support, the starting salary of college graduates was higher. The findings suggest that university-industry cooperation activities must focus on qualitative performances rather than quantitative approaches.